Is conduct after capture training sufficiently stressful? - Wisén, Niclas; Larsson, Gerry; Risling, Mårten; Arborelius, Ulf (Frontiers in Psychology, 2022)
Conduct after capture (CAC) training is for personnel at risk of being captured. To be effective, it needs to be stressful. But how do we know if it is stressful enough? This study uses biomarkers and cognitive measures to evaluate CAC. Soldiers undergoing CAC were measured by the stress hormone cortisol from saliva samples at baseline and during training. The training consisted of being taken capture and put through a number of realistic and threatening scenarios, targeting survival strategies taught in the preceding week. Between scenarios, the trainees were held in a holding cell where they were monitored by a guard. The saliva samples were taken in conjunction with the scenarios. The whole training took place over a period of ~24 h. Cognitive performance was measured at baseline and after training. Three groups took part Group A (n = 20) was taken after 48 h of intense tasks leaving them in a poor resting state. Group B (n = 23) was well rested at CAC onset. Group C (n = 10) was part of a survival, evasion, resistance, and escape (SERE) instructor course. The CAC training was the same for all groups. Group A exhibited a high increase in cortisol during CAC, compared to baseline levels were multiple times as high as “expected” values. Group B exhibited elevated levels slightly lower than those of group A, they also “dropped” to “normal” levels during the latter part of the exercise. Group C displayed the least increase with only slightly elevated levels. CAC training is stressful and cortisol levels were elevated enough to satisfy the prerequisite for effective stress inoculation. No cognitive performance drop could be identified; however, several participants “froze” during the exercise due to intensive stress.